Atmosphere‐ocean linkages in the eastern equatorial Pacific over the early Pleistocene. (2nd May 2016) - Povea, Patricia; Cacho, Isabel; Moreno, Ana; Pena, Leopoldo D.; Menéndez, Melisa; Calvo, Eva; Canals, Miquel; Robinson, Rebecca S.; Méndez, Fernando J.; Flores, Jose‐Abel
Abstract: Here we present a new set of high‐resolution early Pleistocene records from the eastern equatorial Pacific (EEP). Sediment composition from Ocean Drilling Program Sites 1240 and 1238 is used to reconstruct past changes in the atmosphere‐ocean system. Particularly remarkable is the presence of laminated diatom oozes (LDOs) during glacial periods between 1.85 and 2.25 Ma coinciding with high fluxes of opal and total organic carbon. Relatively low lithic particles (coarse and poorly sorted) and iron fluxes during these glacial periods indicate that the increased diatom productivity did not result from dust‐stimulated fertilization events. We argue that glacial fertilization occurred through the advection of nutrient‐rich waters from the Southern Ocean. In contrast, glacial periods after 1.85 Ma are characterized by enhanced dust transport of finer lithic particles acting as a new source of nutrients in the EEP. The benthic ecosystem shows dissimilar responses to the high productivity recorded during glacial periods before and after 1.85 Ma, which suggests that the transport processes delivering organic matter to the deep sea also changed. Different depositional processes are interpreted to be the result of two distinct glacial positions of the Intertropical Convergence Zone (ITCZ). Before 1.85 Ma, the ITCZ was above the equator, with weak local winds and enhanced wet deposition of dust. After 1.85 Ma, the glacial ITCZ was displaced northward, thus bringing stronger winds and stimulating upwelling in the EEP. The glacial period at 1.65 Ma with the most intense LDOs supports a rapid southward migration of the ITCZ comparable to those glacial periods before 1.85 Ma. Key Points: Atmosphere‐ocean coupled changes in the EEP region along the early Pleistocene Two phases are observed in the glacial reorganization of the ITCZ Distinct transport mechanisms of carbon toward the deep sea were characterized